(untitled) (African Journal of Biomedical Research, 2021)
Although they are pathophysiologically involved, evidences inconsistently highlight a relationship between type 2 diabetes mellitus (T2DM) and its prognosis with variation in circulating levels of each of bile acids (BAs) and Insulin-like growth factor-1 (IGF-1). We aimed to investigate the possible role of BAs and IGF-1 in the prediction of T2DM and its complications in Saudi patients. Their fasting plasma levels were correlated to each other and to the disease clinical and biochemical prognostic indices. This is an analytical cross-sectional Tertiary care center-based study. We consecutively included 184 hospital-diagnosed T2DM patients and 113 healthy controls from their accompanying relatives. Anthropometrics, demographics and disease history were recorded. Fasting plasma Levels of total BAs, lipids and glucose were assayed colorimetrically, and, total IGF-1, hemoglobin A1c (HbA1c), insulin, and C-reactive protein (CRP) were assayed. Atherogenic index of plasma (AIP) and homeostatic model assessment of insulin resistance (HOMA-IR) were calculated. Diabetic patients were stratified by disease severity score and treatment score for association analysis. Correlations among parameters were assessed. Area under the receiver operating characteristic (ROC) curve (AUC) assessed the discriminative power of BAs and IGF-1 vs. prognostic indices. Our main outcomes were correlation among BAs and IGF-1 with diabetes prognostic indices. Majority of patients were overweight, females, <60 years old and had complications. Patients showed significant increase in all studied biochemical parameters than controls, except for total BAs; particularly with advancement of age and BMI. AUC showed that CRP, AIP, IR and HbA1c were better predictors of disease complications and that BAs level was the single best predictor of absence of complications. Binary logistic regression showed that only age and treatment score significantly predicted the presence of complications. In clonclusion, IGF-1 can be a monitoring marker and BAs can predict the absence of complications in T2DM. Further prospective researches are needed to elucidate these conclusions in larger multicenteric and longitudinal studies that take in consideration other limitations of this study. Our limitations include: Being a single-centered cross-sectional study, overwhelming major of complicated diabetes with high HbA1c, and, not measuring the induced post-prandial total and individual BAs levels, and, free IGF-1.